ON FISHERY, MORTALITY RATES AND YIELD PER RECRUIT OF RIBBONFISH TRICHIURUS LEPTURUS LINNAEUS - Narasimham, K A (Indian Journal of Fisheries, 2011)
The months of abundance for Trichiurus lepturus, forming 61.2 to 95.3%of the ribbonfish catches, are October to December with minor peaks in April-Mayand July-August. Majority of the fish caught belonged to the 'O' age group andfish older than 3 years are scarce in the commercial catches